1998
DOI: 10.2307/2991661
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of the Adolescent Male Family Planning Client

Abstract: To adequately serve young males, clinics must take into account their sexual and contraceptive histories. But screening should go beyond traditional family planning techniques to discuss how to improve communication with partners and other lifestyle issues that may interfere with consistent use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 1 publication
1
15
1
Order By: Relevance
“…Contraceptive and condom use in this sample of young Australian hairdressing, automotive engineering, and commercial cookery apprentices was slightly higher than that reported for other similar age populations (Manning et al 2000, Brindis et al 1998, but lower than that reported by others (Tydén et al 2001, Narring et al 2000 Notes: * Significant at 0.01; ** significant at 0.001 (after Bonferroni adjustment for multiple comparisons). 1 OR for regular partner at first intercourse.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Contraceptive and condom use in this sample of young Australian hairdressing, automotive engineering, and commercial cookery apprentices was slightly higher than that reported for other similar age populations (Manning et al 2000, Brindis et al 1998, but lower than that reported by others (Tydén et al 2001, Narring et al 2000 Notes: * Significant at 0.01; ** significant at 0.001 (after Bonferroni adjustment for multiple comparisons). 1 OR for regular partner at first intercourse.…”
Section: Discussioncontrasting
confidence: 71%
“…For example, Brindis et al (1998) found among their sample of 1540 sexually active American males aged 19 or younger attending their first visit to a family planning clinic, 73% (or their partners) used a condom, the oral contraceptive pill, a diaphragm, implant, or injectable hormones at first intercourse. A national survey of Swiss youth aged 16-20 years found that 92.6% of their sample used contraception at first intercourse, and 86.5% used either condoms or the pill (no gender difference) (Narring et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Family planning programs and policies increasingly focus on the male partner's roles and responsibilities in contraceptive decision-making and use (Brindis et al 1998).…”
mentioning
confidence: 99%
“…Swanson and Forrest (1987) studied 35 agencies offering family planning services for males and found that condom distribution and STI screening and treatment were the most common services. Brindis et al (1998) identified the needs of 1,780 sexually active males age 19 years and younger who attended family planning clinics in California as part of the Office of Family Planning Expanded Teen Counseling Program. The main reasons males attended the clinic was for birth control, STI exam, physical examinations, or because their partner or their girlfriend wanted them to come.…”
Section: Introductionmentioning
confidence: 99%